Fabrication and Characterization of YSZ/ScSZ bilayer electrolyte for Intermediate Temperature-Solid Oxide Fuel Cell (IT-SOFC) Application - Awang Mat, Zuraida; Nadaraja, Shri Kumaran; Zakaria, Zulfirdaus; Abu Hassan, Saiful Hasmady; Kar, Yap Boon; Tan, Chou Yong; Somalu, Mahendra Rao (International Journal of Integrated Engineering, 2019)
Solid oxide fuel cell (SOFC) technology has advanced significantly in the recent years, and now is an interest of many renewable energy-related industries to invest. However, the main issue of SOFC is the high operating temperature that negatively influence its performance. To reduce the temperature, a method of using bilayer electrolyte is proposed. In this study, a bilayer electrolyte of Yttria-stabilised Zirconia (YSZ) and Scandia-stabilized Zirconia (ScSZ) is used with the objective to reduce the temperature of SOFC to intermediate temperature ranges. ScSZ has been chosen as an alternative to YSZ due to its superior ionic conductivity and good mechanical properties. To achieve the objective, bilayer YSZ/ScSZ electrolyte has been fabricated at different compositions using cold-pressed method. This paper presents the fabrication and characterization results of the work.